2009
DOI: 10.1093/ndt/gfp630
|View full text |Cite
|
Sign up to set email alerts
|

Urinary properdin excretion is associated with intrarenal complement activation and poor renal function

Abstract: Our results suggest that urinary properdin excretion enhances intrarenal complement activation and thus may contribute to the progression of renal damage in proteinuric states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 35 publications
(45 reference statements)
1
25
0
1
Order By: Relevance
“…We previously showed properdin to be involved in complement activation of renal tubular cells (23) and urinary properdin to be associated with a worsening of renal outcome in proteinuric patients (42). We then identified tubular HS to be the receptor for properdin during proteinuria (17).…”
Section: Discussionmentioning
confidence: 95%
“…We previously showed properdin to be involved in complement activation of renal tubular cells (23) and urinary properdin to be associated with a worsening of renal outcome in proteinuric patients (42). We then identified tubular HS to be the receptor for properdin during proteinuria (17).…”
Section: Discussionmentioning
confidence: 95%
“…The importance of complement activation in tubulointerstitial toxicity was already demonstrated years ago (13,36,37). In vitro and in vivo studies have implicated activation of the AP of complement on tubular epithelial cells and its linkage to renal fibrosis (3, 5, 38, 39).…”
Section: Discussionmentioning
confidence: 99%
“…In proteinuria, properdin is found in the urine and may bind to proximal tubular cells. In vitro it was demonstrated that this properdin activates the AP on renal cells (6,13). Furthermore, the excretion of properdin in urine is correlated with increased urinary levels of the terminal complement cascade complex C5b-9 and with poor renal function (6,13).…”
mentioning
confidence: 99%
“…A previous study (40) in patients with kidney disease demonstrated the presence of properdin in their urine, which was associated with higher levels of urinary soluble C5b-9 and worse renal function. Properdin bound to HK2 cells can induce the generation of C5b-9 on its surface, as previously shown (14).…”
Section: Properdin-directed C3 Deposition On Viable Hk2 Cells Is Inhimentioning
confidence: 87%
“…Heparan sulphate on the surface of PTECs acted as a binding site for properdin, binding that can be inhibited by heparinoids (46,47). In addition, excretion of properdin in urine was associated with complement activation products and worse renal outcome in patients with at least 1 g/day of proteinuria in diabetic nephropathy and glomerular disease cases (40).…”
mentioning
confidence: 99%